Inductive heating of fluidized beds: Spray coating process - Idakiev, Vesselin V.; Steinke, Claudia; Sondej, Franziska; Bück, Andreas; Tsotsas, Evangelos; Mörl, Lothar (Powder Technology, 2018)
Spray fluidized bed coating is an established process for the treatment of solid particles. Commonly fluidized beds are heated convectively. Another method is inductive heating by electrically conductive particles. In this work spray coating with inductive heating is investigated. Coating experiments with convective or inductive heating and different process parameters (temperature, spraying rate, initial particle diameter, initial bed mass) were realized. Moisture content, particle size distribution and apparent density of the particles were measured, as well as the thickness and porosity of the layer created on the initial particles. Similar results can be obtained by both heating methods, advantages of inductive heating are discussed as well as limitation
Keywords: Inductive heating of fluiized beds; Coating; Layer porosity; MAGNETIC-FIELD